2016
DOI: 10.3329/bmjk.v48i1-2.27093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of amoebic liver abscess patients admitted in a tertiary care hospital

Abstract: Amoebic liver abscess is an important cause of space occupying lesions of the liver, especially in tropical and sub tropical regions. It is the most frequent complication of invasive amebiasis. It may be found in all age groups but relatively rare in children. The signs and symptoms vary according to the severity of illness. The present study was done to evaluate the clinical profile of patients with amoebic liver abscess for age, gender, clinical features, site of abscess, number of abscess, treatment modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…6 In our study, 79% of the abscesses were located in the right lobe of liver, similar to previous studies. 6,9,10 and 78% of our patients had solitary abscesses, similar to a previous report. 6 We encountered multiple liver abscesses in 22% of the patients, similar to the 18-25% incidence of multiple liver abscesses.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…6 In our study, 79% of the abscesses were located in the right lobe of liver, similar to previous studies. 6,9,10 and 78% of our patients had solitary abscesses, similar to a previous report. 6 We encountered multiple liver abscesses in 22% of the patients, similar to the 18-25% incidence of multiple liver abscesses.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 Similarly our study did not correlate with some other studies. 8,9 In our study we found male to female ratio 8:1 which was similar to others. 6,9 Most of the patient are economically poor and lives in rural area.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations